Value of intracellular bacteria detection in the diagnosis of ventilator associated pneumonia. Issue 4 (April 1996) - Torres, A; El-Ebiary, M; Fábregas, N; González, J; de la Bellacasa, J P; Hernández, C; Ramírez, J; Rodriguez-Roisin, R
Abstract : BACKGROUND: Markers of ventilator associated pneumonia are of interest for confirming the diagnosis and for guiding the initial management of this frequent complication of mechanical ventilation. The detection of intracellular organisms in the polymorphonuclear leucocytes (PMNLs) and/or macrophages of bronchoalveolar lavage (BAL) fluid has been suggested as a specific test for the early indication of an infectious pulmonary process. METHODS: The diagnostic value of detecting intracellular organisms in two types of BAL fluid–protected (P-BAL) and conventional (C-BAL)–in 25 patients who died in one unit was prospectively studied. Immediately after death both P-BAL and C-BAL were performed bilaterally. Through a minithoracotomy on both sides of the chest bilateral bronchoscopically guided open lung biopsy samples were obtained from the same area, and an average of eight open lung blind biopsy samples (not bronchoscopically guided) were taken from each lung for histological examination. BAL fluid was examined for quantitative cultures (threshold 10(4) cfu/ml) and for the presence of intracellular organisms and extracellular organisms, and differential cell counts were also performed. RESULTS: Using the histopathology of the bronchoscopically guided open lung biopsies as the gold standard, detection of intracellular organisms in P-BAL (> or = 5%) and C-BAL (> or = 5%) fluids yielded 75% and 57% positive predictive values, and 83% negative predictive values, respectively. Prior treatment with antibiotics decreased the positive and negative predictive values of intracellular organism detection for both types of BAL fluid. The presence of intracellular organisms was correlated with the quantitative cultures of P-BAL and C-BAL samples. Quantitative cultures from P-BAL fluid were less sensitive (22% versus 45%) and more specific (100% versus 55%) than those from C-BAL samples. The percentage of extracellular organisms and the differential cell count in P-BAL and C-BAL samples could not discriminate between the presence or absence of pneumonia. CONCLUSIONS: The presence of > or = 5% intracellular organisms infecting PMNLs or macrophages in P-BAL or C-BAL fluids is a specific marker of ventilator associated pneumonia.